Granulocyte transfusions in the management of invasive fungal infections. (14th March 2017) - West, Kamille A.; Gea‐Banacloche, Juan; Stroncek, David; Kadri, Sameer S.
Summary: Granulocyte transfusions have a long history of being used in patients with neutropenia or neutrophil dysfunction to prevent and treat invasive fungal infections. However, there are limited and conflicting data concerning its clinical effectiveness, considerable variations in current granulocyte transfusion practices, and uncertainties about its benefit as an adjunct to modern antifungal therapy. In this review, we provide an overview on granulocyte transfusions and summarize the evidence on their role in the prevention and treatment of invasive fungal infections.